Design of an international, phase IV, open-label study of simoctocog alfa in women/girls with hemophilia A undergoing surgery (NuDIMENSION) - Natascha Marquardt; Florian Langer; Katharina Holstein; María Teresa Álvarez Román; Ramiro Núñez Vázquez; Predrag Miljić; Nicolas Drillaud; Laurent Ardillon; Anna-Elina Lehtinen; Rita Carlotta Santoro; Mariasanta Napolitano; Sergio Siragusa; et al. (Therapeutic Advances in Hematology, 2024)
Background: Although hemophilia A mainly affects males, carriers (defined as females with hemophilia A, as well as symptomatic or asymptomatic hemophilia A carriers) are at risk of excessive bleeding, particularly during trauma or during surgical procedures. Clinical trials have focused on male patients with severe disease, and data for females are limited. Improved, evidence-based treatment guidelines for management of hemophilia A carriers are required. Objectives and design: The NuDIMENSION study is a phase IV, prospective, open-label, single-arm study that will evaluate the perioperative efficacy and safety of simoctocog alfa (Nuwiq ® ), a recombinant factor VIII (FVIII), in women/girls with hemophilia A undergoing major surgery. The study will be conducted at approximately 15 centers worldwide. Women/girls aged ⩾12 years, with mild or moderate hemophilia A (residual FVIII activity (FVIII:C) ⩾1% to <40%) and with no current/past FVIII inhibitors are eligible. All patients must be scheduled to undergo a major surgical procedure during which simoctocog alfa will be administered. Methods and analysis: The primary endpoint is overall perioperative hemostatic efficacy (“success” or “failure”) of simoctocog alfa. Hemostatic efficacy will be assessed at the end of surgery and at the end of the postoperative period (i.e., completion of wound healing), with overall adjudication by an Independent Data Monitoring Committee. Safety endpoints will include the incidences of thrombotic events and FVIII inhibitor development. The aim is to recruit 28 patients to achieve 26 evaluable surgeries. Ethics: Ethical approval will be received from institutional review boards/independent ethics committees, and the study will be conducted in compliance with the Declaration of Helsinki. Discussion: Data from NuDIMENSION will generate much-needed evidence on surgical management of women/girls with hemophilia A, which will help to enable the development of treatment guidelines specific for such patients. Trial Registration: CT EU 2022-502061-17-00; NCT05936580